2020
DOI: 10.1126/sciadv.aaz5512
|View full text |Cite
|
Sign up to set email alerts
|

Tipping points of Mississippi Delta marshes due to accelerated sea-level rise

Abstract: Coastal marshes are threatened by relative sea-level (RSL) rise, yet recent studies predict marsh survival even under the high rates of RSL rise expected later in this century. However, because these studies are mostly based on short-term records, uncertainty persists about the longer-term vulnerability of coastal marshes. We present an 8500-year-long marsh record from the Mississippi Delta, showing that at rates of RSL rise exceeding 6 to 9 mm year−1, marsh conversion into open water occurs in about 50 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 43 publications
5
77
1
Order By: Relevance
“…A recent global‐scale prediction of coastal wetland extent for the remainder of this century (Schuerch et al., 2018) has suggested that even under pessimistic climate scenarios, and provided that there is room for landward migration, coastal wetland area will generally increase, echoing previous model studies that have suggested that coastal marshes can keep up with rates of sea‐level rise as high as 10–50 mm yr −1 (Kirwan et al., 2016). These results stand in stark contrast with studies based on the geologic record that show tipping points for marsh drowning in the Mississippi Delta (USA) at rates of relative sea‐level rise (RSLR) of ∼3 mm yr −1 (Törnqvist et al., 2020) and an inability of mangroves worldwide to initiate sustained accretion when rates of RSLR exceed ∼6 mm yr −1 (Saintilan et al., 2020). The main purpose of this Commentary is to examine these seemingly contradictory outcomes.…”
Section: Introductioncontrasting
confidence: 78%
See 1 more Smart Citation
“…A recent global‐scale prediction of coastal wetland extent for the remainder of this century (Schuerch et al., 2018) has suggested that even under pessimistic climate scenarios, and provided that there is room for landward migration, coastal wetland area will generally increase, echoing previous model studies that have suggested that coastal marshes can keep up with rates of sea‐level rise as high as 10–50 mm yr −1 (Kirwan et al., 2016). These results stand in stark contrast with studies based on the geologic record that show tipping points for marsh drowning in the Mississippi Delta (USA) at rates of relative sea‐level rise (RSLR) of ∼3 mm yr −1 (Törnqvist et al., 2020) and an inability of mangroves worldwide to initiate sustained accretion when rates of RSLR exceed ∼6 mm yr −1 (Saintilan et al., 2020). The main purpose of this Commentary is to examine these seemingly contradictory outcomes.…”
Section: Introductioncontrasting
confidence: 78%
“…A striking illustration is provided by the stratigraphic record from the Mississippi Delta where during the early Holocene, when rates of RSLR approached 10 mm yr −1 , incipient (or fringing) marshes only a few kilometers wide rapidly migrated landward with rising sea level. This resulted in thin marsh strata (typically a few decimeters or less) that quickly drowned and were overlain by open-water (lagoonal) deposits (Törnqvist et al, 2020). Only when RSLR decelerated to rates <3 mm yr −1 ∼7,000 years ago, the Mississippi Delta as we know it today started to form by means of rapid shoreline progradation (on the order of 100-150 m yr −1 ; Chamberlain et al [2018]) and associated marsh expansion, echoing delta initiation on a global scale around this time (Stanley & Warne, 1994).…”
Section: The Importance Of Timescalementioning
confidence: 99%
“…Though difficult to quantify, the societal benefits (i.e., ecosystem services) provided by coastal ecosystems in Louisiana's Mississippi River Delta have been valued to be at least $12–$47 billion (US dollars) per year (Batker et al, 2010). However, the rate of wetland loss in Louisiana has been very high in the past century, due to a combination of natural and human factors that have reduced the ability of wetlands to build elevation to keep pace with high rates of subsidence and relative sea‐level rise (Blum & Roberts, 2009; Day et al., 2007; Törnqvist, Jankowski, Li, & González, 2020). Between 1932 and 2016, Louisiana lost approximately 4,833 km 2 of wetlands (Couvillion, Beck, Schoolmaster, & Fischer, 2017), and the state has become a prominent global example of the negative linkages between high relative sea‐level rise, sediment delivery alterations and coastal wetland loss (Jankowski, Törnqvist, & Fernandes, 2017; Twilley et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Tidal marshes provide many well‐documented ecosystem services, including habitat or forage for important fisheries (Boesch & Turner, 1984; Kneib, 1997; Minello et al, 2012), filtering and detoxifying terrestrial runoff (Brin et al, 2010; Nelson & Zavaleta, 2012), and buffering coasts from wave energy and storms (Cochard et al, 2008; Gedan et al, 2011; Knutson et al, 1982). At the same time, tidal marshes face several threats, most notably from accelerating sea level rise (Crosby et al, 2016; Törnqvist et al, 2020), reductions in sediment supply (FitzGerald & Hughes, 2019), impediments to landward migration (Schuerch et al, 2018; Spencer et al, 2016; Thorne et al, 2018), and land reclamation (Ewers Lewis et al, 2019; Gu et al, 2018). Marsh peats found well below present‐day sea level in offshore settings provide examples of marshes that did not keep pace with prehistoric sea level rise (Emery et al, 1965; Wolters et al, 2010).…”
Section: Introductionmentioning
confidence: 99%